2022
DOI: 10.1038/s41467-022-32548-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional electron ptychography of organic–inorganic hybrid nanostructures

Abstract: Three dimensional scaffolded DNA origami with inorganic nanoparticles has been used to create tailored multidimensional nanostructures. However, the image contrast of DNA is poorer than those of the heavy nanoparticles in conventional transmission electron microscopy at high defocus so that the biological and non-biological components in 3D scaffolds cannot be simultaneously resolved using tomography of samples in a native state. We demonstrate the use of electron ptychography to recover high contrast phase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Copyright 2020 Springer Nature. (g–i) Reprinted with permission from ref . Copyright 2022 Springer Nature.…”
Section: Local Structural Order and Defects Characterized By Electron...mentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2020 Springer Nature. (g–i) Reprinted with permission from ref . Copyright 2022 Springer Nature.…”
Section: Local Structural Order and Defects Characterized By Electron...mentioning
confidence: 99%
“…The phase information on biological specimens can also be resolved in 3D by integrating electron ptychography with tomography. A recent study demonstrated the 3D phase reconstruction for the unstained DNA origami with Au NPs . A tilt series of ptychography-based tomography was performed in the tilting range of ±70° with a defocused electron probe of approximately 120 nm diameter.…”
Section: Local Structural Order and Defects Characterized By Electron...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ptychographic tomography exhibited ~2-nm resolution in three dimensions at low-dose conditions (Fig. 5C) ( 45 ).…”
Section: Depth-resolution Analysismentioning
confidence: 99%
“…On the basis of two-dimensional (2D) coherent diffraction patterns acquired at 2D scan positions, which form the so-called 4D dataset, direct ptychographic methods [Wigner distribution deconvolution (WDD) or single side-band (SSB)] are highly dose efficient (28,29) and have the ability of live imaging (30,31). Both WDD and SSB are able to image beam-sensitive materials at higher contrast and spatial resolution (4,32,33). For example, an information limit of 2 Å has been demonstrated in zeolite with SSB (4).…”
Section: Introductionmentioning
confidence: 99%